Evaluation of the Diagnostic Effectiveness of the Cervicari AI Artificial Intelligence Program in Detecting Cervical Intraepithelial Neoplasia (KIUT Publication, 2025)
The rapid development of artificial intelligence in the medical field contributes to the early detection of diseases, improvement of diagnostic accuracy, and reduction of human errors. The CerviCARE AI program is a system that automatically analyzes tele-cervicography images, allowing the detection of intraepithelial changes with high precision. This system is especially important for improving healthcare services in regions where qualified specialists are limited.